COMPARATIVE STUDY OF THE HUMAN TALENT OF THE MEDICAL STAFF OF TWO PUBLIC HOSPITALS OF THE JUNIN REGION IN PERU - Chenet Zuta, Manuel Enrique (2020)
The study aimed to compare the human talentof the medical staff of the Maternal and Child RegionalHospital “El Carmen” with the human talent of the medicalstaff of the Regional Clinical Teaching Hospital “DanielAlcides Carrión” located in the Junín region in Peru. Theresearch was basic type, descriptive cross-sectionaldescriptive design. Two samples of 100 hospital serviceusers each were determined. User selection was notprobabilistic for convenience. The instrument used was anLikert type attitude scale composed of 36 items, arrangedaccording to the seven dimensions in which the variableis composed. To test the hypothesis and find out if thereis a significant difference, the Mann Whitney U test forcomparison of independent samples was used. Accordingto the results, there is no significant difference in thehuman talent of the medical staff between both hospitals,the Mann Withney U test showed a level of significancesig. of 0.230 ? 0.01.